Ultrasound assisted curcumin recovery from Curcuma aromatica: understanding the effect of different operating parameters - Shirsath, Sachin R.; Sable, Sunil S.; Gaikwad, Shashank G.; Gogate, Parag R. (Chemical Engineering and Processing-Process Intensification, 2021)
The present study deals with intensified extraction of curcumin from Curcuma aromatica by employing ultrasound-assisted extraction (UAE) approach also elucidating comparison with the conventional batch extraction to highlight the intensification benefits based on the usage of ultrasound. Understanding into the effect of operational parameters like type of solvent, extraction temperature, solid to solvent ratio and raw material size distribution as well as the equipment operating conditions as frequency and power on the extraction yield has been developed. Based on the results for extraction yield, the optimum conditions for UAE approach were 40 degrees C as temperature, 1:30 as solid to solvent ratio, 0.09 mm as the mean particle size, 240 W as ultrasonic power, 22 kHz as ultrasonic frequency and ethanol as the most suitable solvent. Under these optimum conditions, the highest extraction yield of 73.18% was achieved in 2 h whereas batch extraction for 14 h resulted in 52.31% yield clearly demonstrating the intensification due to ultrasound. Peleg's model was applied to explain the extraction kinetics of curcumin and the proposed model satisfactorily predicted the rates of extraction of cur cumin. Overall, UAE proved to be a better technique in terms of lesser time, lesser heating requirement and additional extraction yield.
Keywords: Cavitation; Curcuma aromatica; curcumin; Intensification; Kinetic modelling; Ultrasound assisted extraction